Reframing the association and significance of co-morbidities in heart failure - Triposkiadis, Filippos; Giamouzis, Gregory; Parissis, John; Starling, Randall C.; Boudoulas, Harisios; Skoularigis, John; Butler, Javed; Filippatos, Gerasimos (European journal of heart failure, 2016)
Several co‐existing diseases and/or conditions (co‐morbidities) are present in patients with heart failure (HF), with diverse clinical relevance. Multiple mechanisms may underlie the co‐existence of HF and co‐morbidities, including direct causation, associated risk factors, heterogeneity, and independence. The complex inter‐relationship of co‐morbidities and their impact on the cardiovascular system contribute to the features of HF, both with reduced (HFrEF) and preserved ejection fraction (HFpEF). The purpose of this work is to provide an overview of the contribution of major cardiac and non‐cardiac co‐morbidities to HF development and outcomes, in the context of both HFpEF and HFrEF. Accordingly, epidemiological evidence linking co‐morbidities to HF and the effect of prevalent and incident co‐morbidities on HF outcome will be reviewed.